DESIGNING ANALOG-DIGITAL SYSTEMS IN SIMULATION PROGRAMMES - Pawel, PTAK (Trends in education, 2014)
Article presents information about design and operation of programs to simulate analog-to-digital systems. Describes two software packages APLAC and MatLab. In both programs discussed examples of simulation systems and presented the results of their simulation and modeling.
Keywords: simulation; designing; systems analog-to-digital.